Light‐Activated Nanoprobes for Biosensing and Imaging. Issue 45 (1st October 2018) - Li, Mengyuan; Zhao, Jian; Chu, Hongqian; Mi, Yongsheng; Zhou, Zehao; Di, Zhenghan; Zhao, Meiping; Li, Lele
Abstract: Fluorescent nanoprobes are indispensable tools to monitor and analyze biological species and dynamic biochemical processes in cells and living bodies. Conventional nanoprobes have limitations in obtaining imaging signals with high precision and resolution because of the interference with biological autofluorescence, off‐target effects, and lack of spatiotemporal control. As a newly developed paradigm, light‐activated nanoprobes, whose imaging and sensing activity can be remotely regulated with light irradiation, show good potential to overcome these limitations. Herein, recent research progress on the design and construction of light‐activated nanoprobes to improve bioimaging and sensing performance in complex biological systems is introduced. First, recent innovative strategies and their underlying mechanisms for light‐controlled imaging are reviewed, including photoswitchable nanoprobes and phototargeted nanosystems. Subsequently, a short highlight is provided on the development of light‐activatable nanoprobes for biosensing, which offer possibilities for the remote control of biorecognition and sensing activity in a precise manner both temporally and spatially. Finally, perspectives and challenges in light‐activated nanoprobes are commented. Abstract : Strategies for developing nanoprobes that can be activated with the high spatial and temporal precision of light and their innovative applications for bioimaging and biosensing are summarized, including photoswitchable nanoprobes for improving the capability of signal identification, phototargeting nanoprobes for enhancing spatiotemporal targeting, and light‐activatable sensing probes for personalizing the detection modality with high accuracy.